THE PORTRAYAL LOVE AND SAD OF CHARACTER’S EMOTIONAL IN REVOLUTIONARY ROAD MOVIE - Ramadhan, Tri Rachmad; Dewi, Nurmala; Aprilia, Aprilia (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2023)
The choice of research object in the film Revolutionary Road is because the narrative contained in the film Revolutinary Road discusses matters that are very closely related to the phenomenon of mental readiness in households as is often the case in Indonesian society today.In this thesis there is a formulation of the problem, namely how the writer tries to discuss the emotions reflected in the character of April Wheeler in the film entitled Revolutionary Road, as well as explaining the factors that cause emotions to arise in this character. The type of research used in this study is a qualitative descriptive approach method obtained through library research. The conclusion of this thesis is that the author explains what emotions are reflected in the character April in the film Revolutionary Road by associating several types of emotions namely Happiness, Love, Sadness, Anger, Fear, Surprise response, Hate, Mood, and Tempramen. Regarding the emotional disturbance experienced by the character April. In addition, explaining the internal factors according to Hurlock and Cole (as quoted by Rismalinda, 2017, p.248) regarding the emotional disturbance experienced by the character April.